Measurement of Odour on Source of Drinking Water Using Threshold Odour Number and Modified Olfactometry - Yusoff, Syafinah (International Journal of Integrated Engineering, 2019)
Concerns on odour of water have increased rapidly. However, odour measurement in water for drinking sources has yet to be established in Malaysia. More study is needed for an approach to quantify the odour incidences in water supply, one that is effective and applicable as a guideline towards the early identification of contamination occurrences. Thus, the objective of this study was to identify correlation (if any) between Threshold Odour Number (TON) test with a portable olfactometry plus odour wheel (POPOW) combination method for assessing odour in drinking water. Water samples collected from a drinking water supply system was tested for odour concentration as well as its character based on an odour wheel. Results from the Pearson correlation showed that the TON and POPOW gave the r-value of 0.833 which indicates that both method highly correlate with a level of confidence of 99 percent. Sample water that was taken near the main source of drinking water was given off as earthy smell, indicating geosmin as a likely contaminant. On the other hand, treated water samples taken directly at the treatment plant had a distinctive, chlorinous odour, which was expected from it use of chlorine as a disinfectant. This study has demonstrated the effectiveness of the portable olfactometer and odour wheel combination method for detecting odour in drinking water supply with at par results to the standard TON. More importantly, POPOW would enable the assessment of odour at site and at a shorter test preparation time, traits which are important especially for remotely located sites.